5x-(2x-1)\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix}3x+3-x+25x-2x+1\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix}x<-5\\ x<\frac{1}{3}\end{matrix}\right.\Rightarrow x<-5" alt="\left\{\begin{matrix}3(x+1)-(x-2)<x\\ 2>5x-(2x-1)\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix}3x+3-x+25x-2x+1\end{matrix}\right.\Leftrightarrow \left\{\begin{matrix}x<-5\\ x<\frac{1}{3}\end{matrix}\right.\Rightarrow x<-5" align="absmiddle" class="latex-formula">
![-6<1-2x\leq 7\Leftrightarrow -7<-2x\leq 6\Leftrightarrow -3\leq x<\frac{7}{2} -6<1-2x\leq 7\Leftrightarrow -7<-2x\leq 6\Leftrightarrow -3\leq x<\frac{7}{2}](https://tex.z-dn.net/?f=-6%3C1-2x%5Cleq%207%5CLeftrightarrow%20-7%3C-2x%5Cleq%206%5CLeftrightarrow%20-3%5Cleq%20x%3C%5Cfrac%7B7%7D%7B2%7D)
![y=-x+8\wedge y=4x+6\\\left\{\begin{matrix}-x+8<0\\ 4x+6<0\end{matrix}\right.\Rightarrow x\in \varnothing y=-x+8\wedge y=4x+6\\\left\{\begin{matrix}-x+8<0\\ 4x+6<0\end{matrix}\right.\Rightarrow x\in \varnothing](https://tex.z-dn.net/?f=y%3D-x%2B8%5Cwedge%20y%3D4x%2B6%5C%5C%5Cleft%5C%7B%5Cbegin%7Bmatrix%7D-x%2B8%3C0%5C%5C%204x%2B6%3C0%5Cend%7Bmatrix%7D%5Cright.%5CRightarrow%20x%5Cin%20%5Cvarnothing)